Medulloblastoma in a calf of the flemish breed - De Cristo T.G.* (2019)
© 2019 Universidade Estadual de Londrina. All rights reserved.Medulloblastomas are neuroectodermal tumors of embryonic origin developing in cerebellum and spinal cord and have an unusual occurrence. When occurs in cattle, it is observed in neonatal cases, leading to multiple neurological clinical signs. Flemish cattle are considered at risk of extinction and the rare specimens of Brazil are in Lages, Santa Catarina. The case of a two-month-old calf with difficulty to remain in a standing position, imbalance, opisthotonus, strabismus, and broad-based gait is described in this study. The animal was euthanized and the necropsy showed an irregular, whitish pink, and friable mass in the cerebellar vermis region, measuring 5×6×3.8 cm associated with the dilation of the lateral ventricles, which extended through the interventricular foramen, midbrain aqueduct, and fourth ventricle. Histologically, it presented elongated triangular neuronal cells arranged in a dense sheet that sometimes encircled small areas of neuropil to form Homer-Wright pseudorosettes. These tumor characteristics were compatible with a medulloblastoma. The immunohistochemical (IHC) evaluation of the tumor demonstrated a positive staining for vimentin in neoplastic cells and glial fibrillary acidic protein in neoplastic stromal cells, non-reactive for synaptophysin, and negative for S100 protein and pan-cytokeratin. The histological and topographical characteristics were paramount for determining the medulloblastoma diagnosis and the IHC panel is similar to that observed in other studies. Tumor growth is limited by skull bony structures, allowing determining that the clinical signs expressed by the animal were directly related to the compression of important functional structures due to tumor expansion. Medulloblastoma is an unusual tumor in all animal species, not previously reported in Flemish cattle, and necropsy followed by histopathological examination is essential for diagnosis.